Маркетингове управління конкурентоспроможністю підприємства - Жовновач, P. І.; Zhovnovach, R. (КНТУ, 2013)
Стаття присвячена дослідженню маркетингового управління конкурентоспроможністю підприємств. Визначено сутність маркетингового управління конкурентоспроможності підприємств, виділено її складові та встановлено взаємозв’язок з функціями менеджменту. Представлено концепцію маркетингового управління конкурентоспроможністю підприємства, що спрямовується на отримання ним в довгостроковій перспективі конкурентних переваг. The article is devoted to the study of marketing management of enterprise competitiveness. The purpose of this paper is the research and development of theoretical principles of marketing management competitiveness. To this end, an analysis of marketing theory to establish the essence of marketing management of the competitiveness of enterprises, in accordance with which it is presented as a major ingredient of the overall management of the enterprise, aimed at obtaining a competitive advantage due to the formation of mutually beneficial relationships among manufacturers, consumers and other parties exchange. A relationship marketing management competitiveness of the enterprises with the performance of the functions of management: analysis, planning, organization, motivation and control of the company. Presented concept of competitiveness of enterprise marketing management, aimed at promoting enterprise adaptation to the changing environment and a long-term competitive advantage in challenging conditions of today's economy.
Competitiveness of enterprise marketing management
Keywords: конкурентоспроможність підприємства; маркетинг; маркетингове управління; маркетингове управління конкурентоспроможністю підприємств; competitiveness; marketing; marketing management; marketing management competitiveness of enterprises